Power, Positionality, and Policymaking in Higher Education: Reflections on Student Lactation Support Initiatives - Whipps, Mackenzie; Dinour, Lauren; Vancour, Michele (Journal of Women and Gender in Higher Education, 2026)
In recent years, universities have extended lactation protections to students that have been traditionally afforded to paid employees only. Absent federal- and state-level regulation, this expansion has generally been piecemeal, taking place only when “breastfeeding advocates” request (or demand) those protections within their universities. Little research exists on these initiatives or about the breastfeeding advocates themselves. This article describes three examples of student lactation support initiatives on diverse U.S. university campuses. Using a comparative case study approach, the researchers examined the impact of positionality within higher education—and relative power afforded to different positions—on the initiatives and experiences of breastfeeding advocates. It is necessary to raise awareness and critically reflect on power structures to bring about change. The researchers found benefits of empowering students to engage in collective advocacy toward these ends, with practical implications for future U.S. lactation protection in academia. © 2026 NASPA—Student Affairs Administrators in Higher Education.
Keywords: dept.hhs

Community-engaged design of a virtual diabetes prevention program intervention with care coordination - LaMonaca, Katherine; Campbell-Britton, Meredith; Duffany, Kathleen O’Connor; Comerford, Beth P.; Morales, Sofia I.; Ayettey, Rockiy G.; Astudillo, Katia; Swansiger, Mary; Kidd, Claudette; Rue, Bailee; Santilli, Alycia; Njike, Valentine Y.; et al. (BMC Health Services Research, 2026)
The Diabetes Prevention Program (DPP) is an evidence-based approach to prevent Type 2 Diabetes (T2D), the leading cause of morbidity and mortality in the United States. Despite demonstrated benefits, acceptability and uptake of DPPs remain low, especially among communities with low incomes at increased risk for diabetes. The Yale-Griffin Prevention Research Center led the design of a community-engaged virtual DPP (vDPP) intervention and assessed its feasibility of implementation in two contrasting settings.
Keywords: Prediabetes; Prevention; Telemedicine; Type 2 Diabetes; dept.hhs

Cartwheels by Natalie Schriefer - Schriefer, Natalie (Flash Frog, 2025)
Nick’s millionth cartwheel looks like his first: He plants one hand on the grass and then, before I can catch his legs and help, he tumbles into a round-off. For a moment I’m taller than him, and I…
Keywords: dept.hhs

Re-Playing Majora’s Mask, College - Schriefer, Natalie (Medium, 2026)
The guard who calls you a child eventually recants.
Keywords: dept.hhs

Zelda With a Pearl Earring - Schriefer, Natalie (Medium, 2024)
After Nixeu’s “ZELDA [Girl with a Pearl Earring]”
Keywords: dept.hhs

Self-Portrait in the Key of Masc by Natalie Schriefer - Schriefer, Natalie (HAD, 2024)
In the style of WCW’s “This is Just to Say” Today I donated the red dress I wore to that holiday party which you were probably hoping I’d wear again but the truth is I hated the sweetheart neckl
Keywords: dept.hhs

’Backrooms’ Tests the Future of Horror Movies - Schriefer, Natalie (Bloomberg.com, 2026)
The film may determine how much Hollywood is willing to bet on other stories without a clear monster.
Keywords: A24; Backrooms; Bloomberg Graphics; Hollywood; Theater; culture; dept.hhs; gaming; graphic; indie games; internet; movies; opinion column

There's a Specific Type of Grief We Don't Talk About. Yoga Can Help You Process It. - Schriefer, Natalie (Yoga Journal, 2026)
Give yourself permission to feel everything.
Keywords: dept.hhs

Will CorePower Yoga Teachers Actually Go on Strike? - Schriefer, Natalie (Yoga Journal, 2026)
As February 1 draws closer, everyone is asking this question. Here's everything you need to know.

Gay Romance ‘Heated Rivalry’ Is Reigniting a Troubling Debate - Schriefer, Natalie (Bloomberg.com, 2025)
Heated Rivalry, based on the second book in Rachel Reid’s “Game Changers” series, has been a hit for HBO Max. Critics have called the gay romance about hockey players one of the best queer TV shows, praising it as “sexy” and “significant.” Beyond these glowing reviews, though, there is another discourse. Heated Rivalry’s success has reignited an unhealthy debate over who gets to tell the stories of marginalized communities — a debate that has proven harmful to closeted creatives in the past and
Keywords: Art; Career; Environment; Equality; Jordan; NETFLIX INC; NEW YORK TIMES CO-A; Rachel Reid; TWITTER INC; Youtube; dept.hhs; view

What I Learned When I Refused to Give Up on My Most Challenging Yoga Pose - Schriefer, Natalie (Yoga Journal, 2025)
A lesson on leaning into discomfort.
Keywords: dept.hhs

Why a Home Yoga Practice Is Just as Legit as Studio Practice - Schriefer, Natalie (Yoga Journal, 2025)
At-home yoga taught me about flexibility—and perfectionism, too.
Keywords: dept.hhs

Why This Round of Tariffs Feels So Personal - Schriefer, Natalie (Bloomberg.com, 2025)
The dreaded “T” word seems to be on everyone’s mind because consumers know it could mean paying more for what they love.
Keywords: China; Donald John Trump; Lifestyle; Policy; Politics; Raw Materials; Small Business; Trade War; Video Games; White House; dept.hhs; view

Close Reading: HOW WRITING BOOK REVIEWS MADE ME a BETTER WRITER - Schriefer, Natalie (Poets & Writers Magazine, 2024)
Keywords: dept.hhs

How to Handle Online Harassment When It Happens to You - Schriefer, Natalie (Wired, 2024)
41% of adults in the US have been harassed online. If your mentions, inboxes, and DMs are blowing up with hateful comments, here are the technological and psychological tools you need to weather the storm.
Section: tags
Keywords: dept.hhs; how-to; mental health; online harassment; social media; twitter

Video Game Music: Science Explains Why Playing Final Fantasy Songs Is Good for Your Brain - Schriefer, Natalie (Inverse, 2024)
Musical memories are relatively unharmed by dementia.
Keywords: dept.hhs

Video Games and Resilience: Science Explains Why Playing Zelda Is Good For Your Brain - Schriefer, Natalie (Inverse, 2023)
Available to players of any skill level — no Twitch subscribers required.
Keywords: dept.hhs

Nintendo Has a Silent Problem With ‘Zelda’ Film - Schriefer, Natalie; CNN, sexuality She has written for; Think, NBC News; Insider; HuffPost; others. (Bloomberg.com, 2023)
A movie based on the popular video game will be inherently difficult because its recurring protagonist doesn’t speak. And developers have long preferred to keep it that way.
Keywords: Culture; Design; Generic 1st 'SI' Future; MAMMA MIA; MICROSOFT CORP; Markets; NETFLIX INC; NINTENDO CO LTD; Video Games; Women; dept.hhs; view

Funny Women: Query Letter for My Totally Publishable Novel - Schriefer, Natalie (The Rumpus, 2023)
(The previous sentence demonstrates both my market awareness and my forward thinking.)
Keywords: dept.hhs

How To Navigate Your Kid’s Coming Out - Schriefer, Natalie (Scary Mommy, 2024)
Five tips for straight parents on how to make the process a little easier – and what to say.
Keywords: dept.hhs

How A Book From 1985 Unexpectedly Changed My View On My Sexuality - Schriefer, Natalie (HuffPost, 2023)
“I expected a lot of things when I started the novel … but I didn’t think it would feel culturally relevant in 2023.”
Section: Culture & Arts
Keywords: dept.hhs

Opinion: The new Zelda has finally arrived. It’s time for a rethink on video games. - Schriefer, Natalie (CNN, 2023)
I was thrilled when Nintendo released “The Legend of Zelda: Tears of the Kingdom” in May. But the unfettered joy I feel playing Zelda today took me longer to acquire than all 900 Korok seeds. While my parents supported my playing video games growing up, so many others blamed them for ruining lives, writes Natalie Schriefer.
Keywords: dept.hhs

Driving Directions - Schriefer, Natalie (Word Sports, 2023)
START: END: Trumbull High School Sacred Heart University 72 Strobel Road
Keywords: dept.hhs

I Wrote About Not Shaving For A Month — And The Backlash Made One Thing Perfectly Clear - Writer, Natalie SchrieferGuest (HuffPost, 2023)
"Within an hour, I had a dozen emails. By the next morning, there were two dozen more — plus more than 100 Twitter notifications."
Section: HuffPost Personal
Keywords: dept.hhs

Author, Edit Thyself. - Schriefer, Natalie (ASEE Prism, 2023)
The article focuses on providing tips to academics for improving the quality and acceptance chances of their scholarly work during the publishing process. Topics discussed include the benefits of reading work aloud to catch errors, batching tasks like reviewing reference lists and in-text citations, and the importance of carefully formatting tables and figures according to publication guidelines.
Keywords: Editing; Oral reading; Punctuation; Tense (Grammar); dept.hhs

The five queer books that helped me come out | Xtra Magazine - Schriefer, Natalie (Xtra, 2022)
These five recent memoirs are queer books that helped me come out, echoing my own life, sometimes in unexpected ways
Section: Books
Keywords: dept.hhs

Learning Self-Compassion - Distancesays, November 20th-Critical (Into The Spine, 2022)
With a little help from Zelda.
Keywords: dept.hhs

Opinion | The reckless way I avoided student debt - Schriefer, Natalie (NBC News, 2022)
I worked three jobs to avoid student debt. Many students find themselves in a similar vulnerable spot, choosing to either face burnout now or later.
Keywords: dept.hhs

So They Didn’t Say Yes: How A Scholarship Rejection Taught Me to Work Smarter - Schriefer, Natalie (Author, 2022)
Three years ago, I graduated from my MFA program. I wanted to hit the ground running, so right from the start, I crafted myself a ritual: around the first of each month, I’d spend a morning scouring listservs and social media for writing opportunities. I tracked submissions calls, literary magazine
Keywords: dept.hhs

For Kids in the Hospital, Video Games Are Part of Recovery - Schriefer, Natalie (Wired, 2022)
In-house gaming technology specialists play with and support the youngest patients. Plus, research shows that playtime gives literal health points.
Section: tags
Keywords: charity; dept.hhs; gaming culture; health care; video games

Here's Why The 'Don't Say Gay' Bill Won't Work - Schriefer, Natalie (Ms. Magazine, 2022)
The flaw in Florida’s “Don’t Say Gay” bill and Texas's anti-trans child abuse directive: They will hurt LGBTQ kids, students and teens.
Keywords: dept.hhs

How to Cope With Post-Game Depression - Schriefer, Natalie (Wired, 2022)
Congratulations, you beat your favorite video game. Now it’s time to beat the feelings of emptiness.
Section: tags
Keywords: dept.hhs; gaming culture; mental health; psychology; video games

The Complicated Queerness in Breath of the Wild - Schriefer, Natalie (Medium, 2021)
Let’s talk about Bolson and Vilia. CW: Transphobia
Keywords: dept.hhs

The English Teacher Who Taught Me How to Hear - Schriefer, Natalie (The Wisdom Daily, 2021)
Have you listened to yourself recently?
Keywords: dept.hhs

The Complicated Process of Rejecting Heteronormativity | Dame Magazine - Schriefer, Natalie (Dame Magazine, 2021)
For 25 years, I thought I was a great proponent of LGBTQ+ rights. I supported queer friends and acquaintances; I stayed up to date on terms and phrasing; I asked for gender pronouns; I went to Pride. So when I had my first same-sex crush, I thought my transition from ally to community member would
Keywords: dept.hhs

Building Power for Health: CARE’s Community Health Leaders Program - Santilli, Alycia; Morales, Sofia I.; Hodgson, Nora; Williams, Janice M.; Alvarez-Diaz, Isabel; Cole, Ayeisha; Abrams, Jasmine; Breny, Jean M.; O’Connor Duffany, Kathleen (Health Promotion Practice, 2026)
Individuals who face the daily impact of health inequities and their social drivers have knowledge and invaluable insights about solutions that are feasible at the local level. Community organizing is a dynamic and proven approach for building power among residents to identify community priorities, advocate for change, and co-create solutions to community issues, which has been applied to advance community priorities in the public health field. To build on evidence and further cultivate a pathway to strengthen community power and capacity within a public health framework, the Community Alliance for Research and Engagement (CARE), a health equity-focused partnership among Southern Connecticut State University, Yale School of Public Health, and the New Haven community, developed and implemented a new initiative, the Community Health Leaders (CHL) Program. The CHL program provides a model for community-centered leadership development as a strategy for advancing health equity. By equipping residents with the skills and support needed to advocate for change, CHL contributes to strengthening community power. Ultimately, continued investment in programs like CHL has the potential to create responsive public health programs and policies, reduce health inequities, and improve health outcomes. © 2026 Society for Public Health Education
Keywords: advocacy; community health; community organizing; dept.hhs; empowerment; health disparities; health equity; health promotion; lay leader advisors; social determinants of health; training

Introducing “Preservice Pipeline”—Why This Column, Why Now - Knipe, Bob (Journal of Physical Education, Recreation and Dance, 2026)
Future professionals learn to lead through a variety of professional opportunities, and it is time that JOPERD provides a forum dedicated to their development and an opportunity for them to lead as authors and coauthors. This article describes the new Preservice Pipeline column and how to submit articles. © 2026 SHAPE America.
Keywords: dept.hms

Utilizing the program impact pathways framework for improving COVID-19 vaccine confidence and uptake: demonstrations of multi-sector collaboration from two geographies in Connecticut - Beaulieu, A.; LaMonaca, Katherine; Higginbottom, Jackson; Foster, Jaime; Macklin, Bernard; Muhammad, Tila; Schwartz, Elizabeth; Comerford, Beth; Santilli, Alycia; Duffany, Kathleen; Pérez‐Escamilla, Rafael (Vaccine, 2025)
Keywords: 2019-20 coronavirus outbreak; Biology; Coronavirus disease 2019 (COVID-19); Infectious disease (medical specialty); Medicine; Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2); Virology; dept.hhs

The Business Case for Breastfeeding: Identifying Which Barriers and Facilitators Employers Prioritize When Supporting Breastfeeding Employees in the Workplace - Frieson, Tomeka; Muhammad, Tila; Belyea, Monica; Cole, Ayeisha; Ray, Natasha; Duffany, Kathleen (Journal of Human Lactation, 2026)
Keywords: Breast feeding; Breastfeeding; Phone; Private sector; Public health; Space (punctuation); breastfeeding; breastfeeding barriers; breastfeeding benefits; breastfeeding experience; breastfeeding knowledge; breastfeeding promotion; breastfeeding support; dept.hhs; maternal health; public health; qualitative methods; social support

Komi Can't Communicate: Making Friends and Not Scaring People - Oda, Tomohito; Schriefer, Natalie (2026)
Learn to make friends and stop scaring people away with this clever book inspired by the hit manga Komi Can’t Communicate.Do you find it hard to sp...

Empowering the self: Flow state in The Legend of Zelda: Breath of the Wild and Tears of the Kingdom - Schriefer, Natalie (Journal of Gaming & Virtual Worlds, 2026)
Keywords: Creativity; Flow (mathematics); Identification (biology); Legend; State (computer science); Tears; dept.hhs

Listening to Community to Improve Breastfeeding Friendliness: Findings From a Community Readiness Assessment on Breastfeeding - Frieson, Tomeka; Masterson, Amelia; Tran, Victoria; Douglass, Frankie; Duffany, Kathleen (Health Promotion Practice, 2025)
Breastfeeding is a key nutritional behavior for infants during their first years of life. While prenatal breastfeeding intentions do not differ significantly between non-Hispanic Black and White mothers, the ability to meet those intentions decreases over time, and to a greater extent among Black mothers. This is partially due to environments inadequately supportive of individuals' breastfeeding needs (i.e., not breastfeeding-friendly). The Community Readiness Assessment is a powerful tool to assess a community's readiness to take action on pressing health issues. While it is frequently used to understand readiness to prevent negative health outcomes, this study explores how it can be used to understand readiness to promote breastfeeding friendliness and subsequently identify appropriate intervention strategies. Between November 2020 and June 2021, we conducted interviews with 23 key respondents in New Haven, Connecticut, representing five community sectors. Respondents scored five dimensions of readiness on a 9-point scale (1 = no awareness, 9 = community ownership). The overall community readiness score was 4.2, denoting the "preplanning" stage of readiness. The highest-scoring readiness dimension was "community knowledge about the issue" (mean score: 4.5), and the lowest-scoring dimension was "resources related to the issue" (mean score: 3.3). Small business owners reported the highest readiness score by sector (mean score: 5.0), while large employers reported the lowest (mean score: 3.1). Scores stratified by both sector and dimension revealed specific areas within the community where readiness-level-appropriate interventions could be implemented. This study highlights the benefit of assessing community readiness prior to intervention to identify tailored, equitable, and effective intervention strategies.
Keywords: Active listening; Breast feeding; Breastfeeding; Breastfeeding promotion; Community Readiness Assessment; Community health; Intervention (counseling); Psychological intervention; Scale (ratio); breastfeeding; breastfeeding-friendly; community; community assessment; community readiness; dept.hhs; public health practice

Flash Fiction: How to Build a Pyramid Fire in the Rain by Natalie Schriefer - Schriefer, Natalie (JMWW, 2021)
Do not walk away from this burgeoning hope of heat and dryness.
Keywords: dept.hhs

Dear Mx. Ortiz – Compressed - Schriefer, Natalie (2021)
Keywords: dept.hhs

The First Step - Schriefer, Natalie (2023)
From a snowbank I watched the squirrel run.
Keywords: dept.hhs

Catch the Moon - Smith, Ed Diane (Independently published, 2020)
Grey Sparrow Press, in this landmark book, cherishes the voices of national writing treasures published over ten years; Robert Bly, Robert Wexelblatt, Michael C. Keith, Jules Nyquist, Khem Aryal, Marie Sheppard Williams [posthumously,] Doug Holder, Momila Joshi, William Woolfitt, Thomas R. Smith, M.J. Iuppa, LB Chhetri, John Roche, and Bhisma Upreti to name a few. Grey Sparrow Press was formed as a non-profit 501[c]3 on May 11, 2009.
Keywords: dept.hhs

Career trajectories of women faculty who became academic administrators - Vancour, Michele L. (Advancing Women in Leadership Journal, 2023)
Women faculty often view academic leadership as incompatible with their work-life balance, detracting from research and teaching commitments, resulting in a loss of autonomy and an abandonment of discipline, promoting change in their relationships with colleagues, and placing an increased emphasis on budgeting, regulations and compliance (DeZure et al., 2014). Many researchers suggest that institutional culture works against leadership development for faculty, making the transition from faculty to administrator unlikely (Barden & Curry, 2013). It is increasingly important to identify the key factors that make the difference for women faculty to assume these roles. As such, in this study qualitative methods were employed to examine the experiences and career trajectories of 16 academic women who held tenured, fully promoted faculty positions prior to becoming administrators. The researcher found evidence to support future recruitment and retention in higher education leadership.
0 citations (Crossref) [2023-10-31]
Keywords: dept.hhs; peer-reviewed

Cold Reality: Revisions of War in John Knowles’ “Phineas” and A Separate Peace – Irish Journal of American Studies - Schriefer, Natalie (Irish Journal of American Studies, 2022)
Keywords: dept.hhs; peer-reviewed; ⛔ No DOI found

The implementation of a nutrition intervention in food pantries: the spirit of SWAP - Morales, Sofia I.; Vicente, Genesis; LaMonaca, Katherine; Rios, Jasmine; Cunningham, Shayna D.; Higginbottom, Jackson; Mathios, Erin; Werlin, Steve; Cramer, James; Santilli, Alycia; O’Connor Duffany, Kathleen (Health Promotion Practice, 2023)
Background. Food insecurity, affecting approximately 10% of the U.S. population, with up to 40% or higher in some communities, is associated with higher rates of chronic conditions and inversely associated with diet quality. Nutrition interventions implemented at food pantries are an effective strategy to increase healthy food choices and improve health outcomes for people experiencing food and nutrition insecurity. Supporting Wellness at Pantries (SWAP), a stoplight nutrition ranking system, can facilitate healthy food procurement and distribution at pantries. Purpose. Guided by the RE-AIM Framework, this study assesses the implementation and outcomes of SWAP as nutritional guidance and institutional policy intervention, to increase procurement and distribution of healthy foods in pantries. Method. Mixed-methods evaluation included observations, process forms, and in-depth interviews. Food inventory assessments were conducted at baseline and 2-year follow-up. Results. Two large pantries in New Haven, Connecticut, collectively reaching more than 12,200 individuals yearly, implemented SWAP in 2019. Implementation was consistent prepandemic at both pantries. Due to COVID-mandated distribution changes, pantries adapted SWAP implementation during the pandemic while still maintaining the ?spirit of SWAP.? One pantry increased the percentage of Green foods offered. Challenges to healthy food distribution are considered. Discussion. This study has implications for policy, systems, and environmental changes. It shows the potential for SWAP adoption at pantries, which can serve as a guide for continued healthy food procurement and advocacy. Maintaining the ?spirit of SWAP? shows promising results for food pantries looking to implement nutrition interventions when standard practice may not be possible.
0 citations (Crossref) [2023-10-31]
Keywords: dept.hhs; peer-reviewed

Coalition Building and Food Insecurity: How an Equity and Justice Framework Guided a Viable Food Assistance Network - Santilli, A.; Lin-Schweitzer, A.; Morales, S.I.; Werlin, S.; Hart, K.; Cramer, J.; Martinez, J.A.; O’Connor Duffany, K. (International Journal of Environmental Research and Public Health, 2022)
Food insecurity is widespread in the United States. The COVID-19 pandemic intensified the need for food assistance and created opportunities for collaboration among historically-siloed organizations. Research has demonstrated the importance of coalition building and community organizing in Policy, Systems, and Environmental (PSE) change and its potential to address equitable access to food, ultimately improving population health outcomes. In New Haven, community partners formed a coalition to address systems-level issues in the local food assistance system through the Greater New Haven Coordinated Food Assistance Network (CFAN). Organizing the development of CFAN within the framework of Collaborating for Equity and Justice (CEJ) reveals a new way of collaborating with communities for social change with an explicit focus on equity and justice. A document review exploring the initiation and growth of the network found that 165 individuals, representing 63 organizations, participated in CFAN since its inception and collaborated on 50 actions that promote food access and overall health. Eighty-one percent of these actions advanced equitable resource distribution across the food system, with forty-five percent focused on coordinating food programs to meet the needs of underserved communities. With the goal of improving access to food while addressing overall equity within the system, the authors describe CFAN as a potential community organizing model in food assistance systems. © 2022 by the authors.
3 citations (Crossref) [2023-10-31]
Keywords: chronic disease prevention; coalition building; dept.hhs; environment change; food insecurity; peer-reviewed; policy; systems